The Links Between Childhood Life Circumstances, Family Persecution and Discrimination Experiences, and Well-Being in Later Life - Jonas Eimontas; Albinas Bagdonas; Antanas Kairys; Olga Zamalijeva; Vilmantė Pakalniškienė; Raimonda Sadauskaitė (Psichologija, 2021)
The life course perspective raised many discussions about continuity, types of threads linking different developmental stages, and ways to identify these links. The aim of this study was to evaluate the significance of childhood family circumstances and family repression / discrimination experiences in predicting psychological well-being in later life. The Survey of Health, Ageing and Retirement in Europe (SHARE) wave 7 data was used; 1985 respondents aged 50+ (M = 66.23, SD = 10.52) living in Lithuania (63.8 % – female) provided retrospective information on their early life circumstances, including home environment, relationships with family / friends, family persecution. Psychological well-being was assessed with a 12-item Control, Autonomy, Self-Realization, and Pleasure (CASP) scale. Results of the hierarchical regression analysis showed that the inclusion of family persecution and other childhood factors increases the prognostic value of the model by 8 percent. Relationships with mother and friends, self-rated health, perceived abilities, number of books at home, and physical harm by others significantly predicted psychological well-being among older adults, even after controlling pivotal sociodemographic variables. These results suggest that creating a caring, safe, and cognitively stimulating childhood environment can promote better development in early stages and contribute to greater psychological well-being in later life.